TINJAUAN HUKUM ISLAM MENGENAI PELAKSANAAN PINJAMAN BANK KELILING DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DUSUN PENGKOLAN - Bella Setya Ningsih; Nabilla Putri (Jurnal Al Wadiah, 2023)
In daily life, people frequently require lenders for immediate requirements or extra funding so that their enterprises can survive. In addition to established financial institutions, the community also has mobile banks that operate independently since they give lending terms and conditions that are convenient. to the society, but are more interested in receiving it back. The goal of this study was to ascertain the methods used in mobile bank loans to raise people's income in Sembung I Subvillage and to learn about the Islamic Legislation governing mobile bank loans in sub-villages within Sembung I. The writers of this study employed a qualitative research methodology. When gathering information from sources and papers in the field connected to the writer by use of observational methods, conversations and records. As the information methods of processing and analysis that the writers employed are analyzed descriptively before being interpreted in the manner of descriptive qualitative analysis. The findings of this study demonstrated that: Initially, Credit from Mobile Banks in raising the standard of living in Sembung I Sub-village, proved to be unable to appreciably raise people's earnings Second, it is against Islamic law for there to be mobile banks that exist with the intention of raising people's income. Since it has aspects of usury, and in actuality, it is mobile Banks cause more harm than good.